Strength Analysis of a Pulp Brick Making Machine with a Capacity of 20 kg/Hour - Bambang Setiawan; Hendro Purwono; Rasma; Gunawan Hidayat; Sri Anastasia Yudistirani (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2026)
Paper is one of the communication tools for administration, and is still the primary choice. In various parts of the world, paper is always used in the fields of economics, education, and so on. From the large number of paper uses, it will have an impact on the amount of paper waste that will be collected, then to meet every paper need, new paper must be produced. One solution in utilizing paper waste that can be done in the home industry is by using a pulp-making machine with unused paper or waste that has been collected to be reused in recycling paper into paper or innovative ones such as pulp bricks. The purpose of this study is to design a model of a pulp-making machine with a frame size of 1100 mm x 800 mm x 835 mm. The design of this machine frame was made to determine the load strength experienced by the frame on a pulp brick-making machine. This study uses load calculations on the frame construction design manually and with the help of the SolidWorks software. The results of the simulation using the software show a maximum von misses value of 410700N/m2 and a safety factor value of 2682.56 N/m. Thus the automatic dishwasher frame is in the safe category.